Determining the Role of Influencers’ Marketing Initiatives on Fast Fashion Industry Sustainability: The Mediating Role of Purchase Intention - Liu, Mengmeng (Frontiers in Psychology, 2022)
Celebrity influence plays a significant role in fostering the consumers’ impulse buying tendency and purchase intention. In the modern advertising era, the celebrity endorsement characteristics have driven the firms’ promotion campaigns, stimulating consumer purchasing behavior through celebrity branding. The study signifies the relationship between celebrity's traits of trustworthiness, attractiveness, credibility, and expertise influence consumers' impulse behavior. The data was collected from the 371 customers of the fast fashion industry by using the convenient-sampling technique. SMART-PLS was used for data analysis by applying structural equation modeling. The study results show that celebrity trustworthiness, the attractiveness of a celebrity endorser, the credibility of a celebrity endorser, and celebrity expertise positively impact purchase Intention and impulse buying tendency. Purchase Intention plays a mediating role between independent and dependent variables.